Health and vulnerability of the LGBT+ population: An integrative review (Research, Society and Development, 2023)
Objective: To identify the existence of health vulnerabilities of the LGBT+ population in the context of health services. Method: Integrative literature review of articles published between 2017 and 2022, based on the search in scientific journals, carried out through an electronic search in the Scielo, PubMed, BDENF and LILACS databases, using the descriptors selected in DeCS /MeSH. Results: Six articles were selected that met the inclusion criteria to achieve the proposed objective, with the largest number of publications coming from PubMed and Scielo. Regarding the main results found, social and gender vulnerabilities were mentioned, difficulty in understanding and preventing STIs, prejudice/domestic violence, abjection and unpreparedness of the health team and religious interference, such as the health vulnerabilities of the population. Final Considerations: In the context of the services, the existence of health vulnerabilities was evidenced, as well as situations that relate to taboos and social and family prejudices, lack of knowledge about STIs and methods of prevention, gender vulnerabilities and social exclusion.